Redefining the Operating Room: Remote Surgery Capabilities Enabled by 5G and Robotics - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The history of surgery is a chronicle of relentless innovation, from the adoption of anesthesia and antisepsis to the advent of minimally invasive techniques...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care